Konsep Dasar Puasa dan I’tikaf - Amalia Ramadhani; Imron Ashari; Muhammad Ngabid Ngadani; Saskia Dwi Agnesia; Nur Wakhid (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Fasting and i’tikaf are important acts of worship in Islam with deep spiritual and social dimensions. This study aims to examine the basic concepts of fasting and i’tikaf and their legal implications in a Muslim’s life. The method used is qualitative research with a library research approach by referring to classical and contemporary Islamic jurisprudence literature. The results show that fasting functions as a means of self-control and increasing piety, while i’tikaf serves as a medium to draw closer to Allah SWT, especially during Ramadan. Both are closely related in shaping a more spiritual and disciplined Muslim personality.